Getting Serious About Serious Games: Best Practices for Computer Games in Reading Classrooms. (12th July 2018) - McTigue, Erin M.; Uppstad, Per Henning
Abstract: Computer games and computer‐assisted instruction have become prevalent in reading classrooms. However, research‐based guidance for teacher use of such resources has not progressed at the same rate. In lieu of research, myths circulate about the utility of these resources, particularly when students use computer games independently. The authors synthesize research regarding computer games for young readers and particularly focus on issues of classroom implementation. This article is structured as a series of myths regarding expectations and best practices with computer games. The authors then present research findings to refute the myths and conclude with practical recommendations for teachers. Final recommendations emphasize the need for young readers to interact more, with adults and peers, in order for the learning that occurs in the computer environment to transfer to authentic reading activities. The authors encourage teachers to draw on pedagogical and content knowledge to be critical consumers of computer resources.